The Effect of Hots-Based Blended Learning on Students’ Critical Thinking Ability in Physical Education Learning (Universitas Negeri Semarang, 2022)
This study intends to investigate the impact of blended learning based on HOTS on the critical thinking skills of Physical Education students. This study’s instrument is based on (Valenzuela et al., 2011), which consists of five components: 1) Wishful Thinking, 2) Project Value Achievement, 3) The Worth of Utility, 4) Task Inherent Worth, and 5) Fee. The employed research approach consisted of a controlled experiment with experimental and control groups. The experimental group was administered the blended learning model based on HOTS, whereas the control group was administered the conventional learning model. Using the paired sample t-test, the data analysis yielded a p-value of 0.000 0.05. Students’ critical thinking skills increased by 87.16 percent as a result of the blended learning paradigm, according to the findings of the study. Therefore, the integrated learning paradigm based on HOTS efficiently trains students’ critical thinking abilities in Physical Education.